2019
DOI: 10.3390/molecules24040804
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of Laurus nobilis L. Essential Oils from Bulgaria

Abstract: Laurel, Laurus nobilis L. is an evergreen plant belonging to the Lauraceae family, native to Southern Europe and the Mediterranean area. This is the first report on the composition and bioactivity of laurel essential oil (EO) from Bulgaria. The oil yield was 0.78%, 0.80%, and 3.25% in the fruits, twigs, and leaves, respectively. The main constituents in the fruit EO were 1,8-cineole (33.3%), α-terpinyl acetate (10.3%), α-pinene (11.0%), β-elemene (7.5%), sabinene (6.3%), β-phellandrene (5.2%), bornyl acetate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 30 publications
6
75
3
1
Order By: Relevance
“…Apricot EO acts against E. coli and Klebsiella pneumoniae with an MFC of 23.4 mg/mL and C. parapsilosis with 11.70 mg/mL. Our findings are in agreement with those reported by several authors for the same species [16,29]. Table 2.…”
Section: Antimicrobial and Synergistic Effect Of Eosupporting
confidence: 92%
See 2 more Smart Citations
“…Apricot EO acts against E. coli and Klebsiella pneumoniae with an MFC of 23.4 mg/mL and C. parapsilosis with 11.70 mg/mL. Our findings are in agreement with those reported by several authors for the same species [16,29]. Table 2.…”
Section: Antimicrobial and Synergistic Effect Of Eosupporting
confidence: 92%
“…The obtained data showed that the composition of the studied laurel EO differed quantitatively to those previously reported in samples from other geographical regions such as Italy, Turkey, Cyprus, Tunisia and Bulgaria. In fact, the concentration of eucalyptol in our samples was lower than the values recorded in Tunisia (56%) [26], Cyprus (58.59%) [27] and Bulgaria (41%) [16]. However, it was higher compared with those found in other studies, namely Algeria (34.62%) [15].…”
Section: Chemical Composition Of the Eoscontrasting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, volatile substances such as EOs derived from plant species with a GRAS (generally recognized as safe) status based on their long history of use have great potential as natural preservatives in the food industry and agriculture, since the U. S. Food and Drug Administration (FDA) approved their safety for food application. Various studies evaluating the antimicrobial activity of some GRAS EO-bearing plant species or their constituents have been previously published [77][78][79], but only a few have directly focused on their vapour phase.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, there is no particular data suggesting synergism between bornyl acetate and other terpenes. Some studies have demonstrated synergism mainly produced between oxygenated terpenes (Sokovic et al 2010;Fidan et al 2019;Bassole and Juliani 2012;Novato et al 2019;Gavaric et al 2015;Jagannath et al 2012). Thus, in further studies, synergism of bornyl acetate with other terpenes should be investigated.…”
Section: Discussionmentioning
confidence: 95%